Apparent Activities in Special Education. A Critical Analysis of Core Curriculum - Jabłoński, Maciej (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
The topic discussed herein concerns a particular deconstruction of the core curriculum in primary special schools carried out by means of a critical analysis of this document. On the grounds of this analysis, the article shows the consequences of apparent actions that are taking place in special schools, which in consequence lead to violence, perpetuating negative stereotypes and stigmatisation of students with intellectual disabilities.